2010
DOI: 10.1007/s10006-010-0219-8
|View full text |Cite
|
Sign up to set email alerts
|

Areca nut in pathogenesis of oral submucous fibrosis: revisited

Abstract: The common etiological factor considered for this unremitting disease is use of areca nut; however, the precise mechanism still remains elusive and controversial. A wide range of treatment consisting of drugs, surgical therapy, and physiotherapy have been attempted till date, with varying degrees of benefit, but none of them have proved to be a cure for this disease. This field remains open for clinical trials and research. This paper aims to give an overview on the role of areca nut in the pathogenesis and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
158
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(163 citation statements)
references
References 84 publications
4
158
0
1
Order By: Relevance
“…It has been demonstrated that arecoline, a major areca nut alkaloid, was found to stimulate human buccal mucosal fibroblasts (BMFs) proliferation and collagen synthesis in vitro [34]. Thus, the increased collagen synthesis or reduced collagen degradation may be a possible mechanism in the development of the disease [1].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that arecoline, a major areca nut alkaloid, was found to stimulate human buccal mucosal fibroblasts (BMFs) proliferation and collagen synthesis in vitro [34]. Thus, the increased collagen synthesis or reduced collagen degradation may be a possible mechanism in the development of the disease [1].…”
Section: Introductionmentioning
confidence: 99%
“…Persistent hepatic inflammation is a hallmark of habitual BQ chewing (Sarma et al, 1992;Lin et al, 2008;Angadi and Rao, 2011) and/or chronic HBV/HCV infection (Bouchard and Navas-Martin, 2011;El-Serag, 2012). Hepatic fibrosis, or cirrhosis, is a common end-stage condition of many chronic liver diseases (Bouchard and Navas-Martin, 2011;Luedde and Schwabe, 2011;El-Serag, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic fibrosis, or cirrhosis, is a common end-stage condition of many chronic liver diseases (Bouchard and Navas-Martin, 2011;Luedde and Schwabe, 2011;El-Serag, 2012). During fibrosis progression, hepatocellular damage and inflammation trigger complex cellular events that result in collagen deposition (Angadi and Rao, 2011;Bouchard and Navas-Martin, 2011;Luedde and Schwabe, 2011;ElSerag, 2012;Kong et al, 2012). Serial liver biopsies are the current gold standard to evaluate the progression of fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations